Enhanced revision rhinoplasty with processed costal cartilage guided by preoperative computed tomography and 3D scanning - Pawel Szychta (SpringerOpen, 2024)
Abstract Background Revision rhinoplasty presents unique challenges, particularly in achieving structural integrity and aesthetic harmony. This study explores the efficacy of costal grafts in addressing these challenges, focusing on anatomical corrections and patient outcomes. Materials and methods A prospective analysis was conducted on patients undergoing revision rhinoplasty with costal grafts. An algorithmic approach was applied to tailor the surgical technique to individual anatomical needs, documented through pre- and postoperative assessments, including CT imaging and 3D scanning. Results A total of 34 patients were included. Significant improvements were noted in nasal structure and function post-surgery. The mean NOSE score improved from 94.47 ± 5.48 preoperatively to 12.59 ± 13.43 postoperatively, and the mean ROE score increased from 18.44 ± 10.02 to 92.65 ± 13.00, indicating substantial enhancement in both nasal airway function and patient satisfaction. The use of costal grafts facilitated effective corrections for a broad spectrum of nasal deformities, with a complication rate of 2.94%. Conclusions Costal grafts in revision rhinoplasty offer a versatile and effective solution for complex nasal deformities. The algorithmic approach used in this study enhances repeatability and outcomes, suggesting a promising avenue for achieving desired aesthetic and functional results in revision cases. Further research is warranted to optimize techniques and evaluate long-term outcomes. Level of evidence II.